Biological, mechanical, optical and physicochemical properties of natural chitin films obtained from the dorsal pronotum and the wing of cockroach. (1st May 2017) - Kaya, Murat; Sargin, Idris; Sabeckis, Ignas; Noreikaite, Deimante; Erdonmez, Demet; Salaberria, Asier M.; Labidi, Jalel; Baublys, Vykintas; Tubelytė, Vaida
Highlights: Natural chitin films were extracted from the dorsal pronotum and the wing of cockroach. Both chitin films consisted of nanofibers and exhibited higher thermal stability. Hydrophobicity and transparency of the wing chitin film was found higher. Two common pathogens could not form biofilms on the surface of the chitin films. The films can be used as surface and food coating material or as a packing additive. Abstract: In previous studies, chitin-based films were produced from chitin nanofibers in dust form and fully characterized. However, chitin films naturally present in many organisms have not been isolated and characterized. Herein, structurally intact chitin films were successfully extracted from the dorsal pronotum and the wing of cockroach . Despite using the same extraction procedure, important differences were observed. Especially, hydrophobicity, transparency, antifungal and antibacterial biofilm activities of wing chitin film were recorded notably higher than those of chitin film from the dorsal pronotum. However, better mechanical properties were observed for chitin film from the dorsal pronotum. Notably, among the tested bacteria, two common pathogens could not form biofilms on the surface of the films. This study clearly demonstrated natural chitin films obtained from an insect can provide a new perspective to chitin-based applications where chitin films with high thermal stability, transparency, resistance to bacterial biofilm formation and antifungal activity are needed.